TRADISI PERNIKAHAN DIBAWAH UMUR DAN DIBAWAH TANGAN MASYARAKAT MADURA SERTA DAMPAK YANG DITIMBULKAN - sudahri sudahri (MEDIAKOM : Jurnal Ilmu Komunikasi, 2021)
One of the classic and very unique traditions on the island of Madura is in the case of underage marriages and underhand marriages (not registered at KUA). This happened in one of the villages, namely Sanadaja Village, Pasean District, Pamekasan Regency. Underage marriage is a marriage where both the bride and groom are under the age range of 14-16 years for women and 15-19 years for men. The existence of the marriage above is due to the strong tradition that has existed since the past and continues to be preserved until modern times as it is today. In addition, religious figures such as kiai, bendoro (lora) and community leaders such as Kalebun (village head), Pangaseppo (traditional leaders) and bajingan (village thugs) are also very influential in maintaining the tradition and become a problem in itself which until now has not been able to be removed from the habits of the local community. This type of research is descriptive qualitative with a phenomenological approach. Data collection techniques were carried out by in-depth interviews and observations.